Analisis Variasi Tras Lompotoo Sebagai Substitusi Parsial Agregat Halus Terhadap Kuat Tekan Beton Self-Compacting Concrete (SCC) - Moh. Rizky Pradana; Kasmat Saleh Nur; Komang Arya Utama (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Self-Compacting Concrete (SCC) is a type of concrete capable of flowing and consolidating under its own weight without mechanical vibration, making it suitable for structures with dense reinforcement and complex geometries. The performance of SCC is highly influenced by its constituent materials, particularly fine aggregates, which affect both workability and compressive strength. This study investigated the use of Lompotoo trass as a partial replacement for fine aggregate in SCC and its impact on workability and compressive strength. Lompotoo trass was used at substitution levels of 5%, 10%, 15%, and 20% of the total fine aggregate volume. A superplasticizer, Sika ViscoCrete 3115 N, was added at 1.5% of cement weight. Workability was evaluated through slump flow, T500 flow time, J-ring, and GTM screen stability tests based on EFNARC (2005) standards, while compressive strength was measured at 28 days. The results showed that all SCC mixtures met the required workability criteria. However, the J-ring test indicated poor passing ability (Category III) for the 5%, 10%, and 20% variations. The highest compressive strength was achieved at 5% substitution, reaching 37.16 MPa, a 23.1% increase compared to the control mixture (30.19 MPa). The 10% and 15% substitutions also improved strength by 17.4% and 12.3%, respectively, while the 20% substitution resulted in a slight decrease of 1.26%. These findings suggest that Lompotoo trass is a promising material for partial fine aggregate substitution in SCC, contributing to improved performance and sustainable concrete development.